Effects of new urban greenways on transportation energy use and greenhouse gas emissions: A longitudinal study from Vancouver, Canada. (July 2018) - Ngo, Victor Douglas; Frank, Lawrence D.; Bigazzi, Alexander Y.
Highlights: First longitudinal study evaluating changes in GHG emissions from an urban greenway. Tracked a cohort of 524 residents over a period of three years from 2012 to 2015. Residents living near the greenway reduced their transport GHG emissions by 21%. Residents living near the greenway reduced their vehicle usage and drove less. Active transport infrastructure can contribute to municipal climate change policy.